2012
DOI: 10.3109/09513590.2012.683071
|View full text |Cite
|
Sign up to set email alerts
|

A potential link of oxidative stress and cell cycle regulation for development of endometriosis

Abstract: HNF-1β in endometriosis might be a factor that controls the cell cycle and DNA damage checkpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…Therefore, elucidating the detailed association between HNF1B upregulation and the acquisition of cell cycle regulation under conditions of oxidative stress may improve understanding of the mechanisms used to repair DNA damage (7). A previous study identified the role of the HNF1B-mediated signaling pathway in a fail-safe mechanism for the oxidative stress-induced DNA damage response (10). The present study identified six genes, F-Box protein 5 (11,12), Cdk5 and Abl enzyme substrate 1 (13), hepatitis A virus cellular receptor 1 (HAVCR1) (14), cyclin E1 (15), tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein, θ (16) and TPD52 (17,18), associated with regulation of the cell cycle regulation that are abnormally expressed in ovarian clear cell carcinoma.…”
Section: Overexpression Of Genes and Their Transcripts In Ovarian Clementioning
confidence: 99%
“…Therefore, elucidating the detailed association between HNF1B upregulation and the acquisition of cell cycle regulation under conditions of oxidative stress may improve understanding of the mechanisms used to repair DNA damage (7). A previous study identified the role of the HNF1B-mediated signaling pathway in a fail-safe mechanism for the oxidative stress-induced DNA damage response (10). The present study identified six genes, F-Box protein 5 (11,12), Cdk5 and Abl enzyme substrate 1 (13), hepatitis A virus cellular receptor 1 (HAVCR1) (14), cyclin E1 (15), tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein, θ (16) and TPD52 (17,18), associated with regulation of the cell cycle regulation that are abnormally expressed in ovarian clear cell carcinoma.…”
Section: Overexpression Of Genes and Their Transcripts In Ovarian Clementioning
confidence: 99%
“…Recent biochemical and immunohistochemical studies have noted a specific expression of HNF-1β in CCC and genetic alteration may be involved in oxidative stress (2)(3)(4). The majority of the CCC-specific genes were associated with the redox-related genes (2).…”
Section: Proposed Function Of Cd44v9mentioning
confidence: 99%
“…These genes have been hypothe sized as key drivers of the phenotypic characteristics. Recent reviews have demonstrated the function of this molecule in the endometriosis and ovarian cancer (2)(3)(4).…”
Section: The Profiles Of Hnf-1β Target Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…11,15 Interestingly, iron-induced reactive oxygen species (ROS) signaling participates in endometriotic cell survival possibly by acting in detoxification and anti-apoptotic pathways through overexpression of HNF-1β. 16,17 However, little is known about the association between HNF-1β expression and inflammatory cytokines, such as NF-κB, in the endometriosis-OCCC sequence. Moreover, the detailed mechanisms that govern HNF-1β-mediated modulation of cell kinetics, including cell proliferation and apoptosis, in OCCCs remain to be clarified.…”
mentioning
confidence: 99%